PENGEMBANGAN BAHAN AJAR BERBASIS PEMBELAJARAN ONLINE UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SMA KELAS X - Nurmia Eliza; Afnaria Afnaria; Syahlan Syahlan (MES: Journal of Mathematics Education and Science, 2021)
The use of teaching materials in schools should pay attention to their impact on students' understanding and critical thinking skills. Teaching materials are one of the media that have the potential to improve students' critical thinking skills. Therefore, teaching materials must meet the requirements of validation, effectiveness, and practicality. For this reason, this study aims to develop online learning-based teaching materials to improve students' critical thinking skills. This research is a development research by applying the Thiagarajan development model and limiting it to define, design, and development. The instruments used are validation sheets, student response questionnaires, and critical thinking skills tests. The trial was conducted on class XMia-1 and XMia-2 students of SMA Budi Insani Medan, each of which amounted to 32 students. The results show that to develop valid, effective, and practical online learning-based teaching materials, it takes hard work to make revisions/improvements as well as criticisms, suggestions, or comments from validators and students.